The Ethical Backlash of Corporate Branding - Basu, K; Palazzo, G (2007)
Past decades have witnessed the growing success of branding as a corporate activity as well as a rise in anti-brand activism. While appearing to be contradictory, both trends have emerged from common sources - the transition from industrial to post-industrial society, and the advent of globalization - the examination of which might lead to a socially grounded understanding of why brand success in the future is likely to demand more than superior product performance, placing increasing demand on corporations with regard to a broader envelop of socially responsible behavior. Directions for strategic and managerial options are suggested.